2021
DOI: 10.21273/hortsci16057-21
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Growth-inhibitory Activity, Mineral Contents, and Functional Components in Different Tissue Parts of Asparagus (Asparagus officinalis L.) and Availability of Unusable Parts

Abstract: Asparagus is a popular vegetable rich in healthy functional components. However, the process of its production leaves ferns from aboveground parts and roots from underground parts as unusable parts, and this is an issue to be resolved. In our previous studies, large amounts of rutin were noted in the cladophylls and storage roots (brown and epidermis), and the protodioscin content was high in buds, in the soil-covered section of spears, and in rhizomes. This study was conducted to examine the distribution of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…On the other hand, when comparing with data from the edible portion reported in other studies, it can be seen that the values of Na and Mg found in this study were similar to those reported by Motoki et al [33] and Moreiras et al [34], while other elements were found in lower amounts. The analyzed edible spears also presented values of Mg similar to those reported by Amaro-López et al [32] for spears of A. officinalis, cv.…”
Section: Mineralssupporting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, when comparing with data from the edible portion reported in other studies, it can be seen that the values of Na and Mg found in this study were similar to those reported by Motoki et al [33] and Moreiras et al [34], while other elements were found in lower amounts. The analyzed edible spears also presented values of Mg similar to those reported by Amaro-López et al [32] for spears of A. officinalis, cv.…”
Section: Mineralssupporting
confidence: 91%
“…Adouni et al [1] studied mineral contents in the root and rhizomes of A. stipularis; the values found in the present work for root by-product of A. officinalis, var Primens were slightly lower for Mg, similar for Ca and much higher for K than values reported by these authors. However, for samples of A. officinalis analyzed by Motoki et al [33], the Ca and Mg content in the roots was similar to those found in this study.…”
Section: Mineralssupporting
confidence: 91%
“…[2] Rutin also has anti-inflammatory and antibacterial properties. [3][4][5] The saponins in A. officinalis have anticancer, anti-inflammatory, and sedative properties. [6] Hence, A. officinalis is widely consumed because of its rich nutritional value and medicinal compositions in plant kingdoms worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a series of antioxidants such as rutin, glutathione, ascorbic acid, and anthocyanins can reduce the reactive oxygen in the human brain and cardiovascular damage [2] . Rutin also has anti–inflammatory and antibacterial properties [3–5] . The saponins in A. officinalis have anticancer, anti‐inflammatory, and sedative properties [6] .…”
Section: Introductionmentioning
confidence: 99%